Vegetation Diversity Quality in Highland Forest of Ranu Regulo Lake Area, Bromo Tengger Semeru National Park, East Java - Jehan Ramdani Haryati; luchman Hakim (Journal of Tropical Life Science, 2012)
Aim of this research was to study vegetation diversity quality in highland forest of Ranu Regulo Lake area in Bromo Tengger Semeru National Park (TNBTS), East Java. Field observation was carried out by vegetation analysis using sampling plots of 25x25 m2 for trees, 5x5 m2 for poles, 1x1 m2 for ground surface plants. Community structure of each lake side was determined by calculating vegetation's density, basal area, frequency, important value and stratification of species. While vegetations diversity was estimated by taxa richness, Shannon-Wiener diversity index, and rate of endemism. Each lake side forests were compared by Morisita community similarity index. The result showed that based on existed vegetation, highland forest surrounding Ranu Regulo Lake consisted of four ecosystems, i.e. heterogenic highland forest, pine forest, acacia forest and bushes. Bushes Area has two types of population, edelweiss and Eupatorium odoratum invaded area. Vegetation diversity quality in heterogenic highland forest of Ranu Regulo TNBTS was the highest, indicated by its multi-stratification to B stratum trees of 20-30m high. Heterogenic highland forests formation was Acer laurinum and Acmena accuminatissima for trees, Chyatea for poles. Taxa richness was found 59 species and 30 families, while the others were found below 28 species and 17 families. Diversity Index of heterogenic highland forest is the highest among others for trees is 2.31 and 3.24 for poles and second in bushes (H=3.10) after edelweiss ecosystem (H=3.39). Highest rate of endemism reached 100% for trees in heterogenic highland forest, 87% for poles in edelweiss area and 89% for bushes also in heterogenic highland forest. Trees, poles and herbs most similarity community showed by pine and acacia forest. Based on those five characters, vegetation diversity quality in Ranu Regulo Lake area was medium for heterogenic highland forest and edelweiss area comparing to pine and acacia forest which had very low diversity quality. This low diversity was caused by invading species E. odoratum in density, distribution and dominance for threatening growth of poles and ground surface plants local species. Invaded ecosystem were pine forest, acacia forest and edelweiss area. It hasnt major invading in heterogenic highland forest, but it has reached the edge. Therefore, environmental policy must focus on this matter soon. Keywords: highland forest, community structure, quality diversity, Ranu Regulo